Enforcement of the Code of Ethics for 2024 Election Organizers in Indonesia: A Substantive Justice Perspective - Didik Suhariyanto; Ade Sathya Sanathana Ishwara; Sinta Dyah Kirana (Magister of Law, Faculty of Law, University of Mataram, 2024)
This study employs a normative legal research approach focusing on conceptual and legislative analysis. Its aim is to examine the dynamics of the enforcement of the electoral organizers’ code of ethics by the Indonesian Election Supervisory Agency (DKPP) and to formulate a reconstruction of this enforcement aimed at achieving substantive justice. The findings assert that the enforcement dynamics of the electoral organizers’ code of ethics by DKPP inherently pose two main issues. Internally, the enforcement requires oversight and public participation to ensure DKPP’s credibility and integrity in upholding the code of ethics. Externally, issues arise regarding the final and binding nature of DKPP decisions, which have been undermined by Constitutional Court rulings, allowing for their annulment by judicial bodies such as the Administrative Court (PTUN). Reconstruction or reform efforts concerning the enforcement of the electoral code of ethics for electoral administrators, based on substantive justice, necessitate a clear affirmation of the independence of ethical norms, particularly those related to the conduct of electoral administrators. This includes ensuring that the enforcement of these ethical norms is immune from legal norms and external intervention. Additionally, there is a need for a revision of the electoral laws in Indonesia to enhance the appeal process for ethical judgments rendered by the Election Supervisory Board (DKPP), which are final and binding and cannot be overturned by the courts, especially the Administrative Court (PTUN).